L1-L2 transfer in ditransitive construction: A usage-based replication study with Turkish speakers of English - Gedik, Tan Arda; Uslu, Fatima (Springer International Publishing, 2023)
Some studies (e.g., Schwartz et al., Language mode vs. L2 interference: Evidence from L1 Polish. ICPhS, 2015) suggest that the transfer between languages is a binary setting, as in, it either happens or does not happen. With recent studies and suggestive evidence from usage-based approaches, it becomes feasible to suggest that the phenomenon of transfer may not be binary but rather gradient (Cabrera & Zubizarreta, Overgeneralization of causatives and transfer in L2 Spanish and L2 English. Selected Proceedings of the 6th Conference on the Acquisition of Spanish and Portuguese as First and Second Languages, 15-30, 2005; Römer et al., Linking learner corpus and experimental data in studying second language learners' knowledge of verb-argument constructions. ICAME Journal, 38(1), 115-135. https://iclc2019.site/wp-content/uploads/abstracts/applied/ICLC-15_paper_202.pdf, 2019). The current study is a replication of Goschler and Stefanowitsch (2019), who tested advanced German speakers of English using an acceptability judgment task and other measures on English ditransitive constructions, tapping into L2 learners' receptive lexicogrammatical knowledge. Goschler and Stefanowitsch (2019) found that even at advanced levels, learners may accept unconventional combinations in the English ditransitive construction that are otherwise strongly attracted to each other in the German ditransitive, suggesting that such structures may not be entrenched enough in the L2 to be judged as ungrammatical, possibly due to L1 influencing this judgment. The transfer effects do not seem to be limited to the ditransitive but seem possible in the intransitive construction as well (Gedik, Collostructional transfer effects in Turkish learners of English: The intransitive-unaccusative construction. Pedagogical Linguistics. https://doi.org/10.1075/pl.22019.ged, 2023). The present study replicates the results, with strongly attracted combinations in the Turkish ditransitive skewing the acceptability of the corresponding unconventional combinations in the English ditransitive. Possible explanations and brief pedagogical implications are discussed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Collostructions; Construction grammar; Ditransitive; Transfer effects; Turkish